Light-triggered oxidative activity of chromate at neutral pH: A colorimetric system for accurate and on-site detection of Cr(VI) in natural water - Liao, Jing; Wu, Yuke; Chen, Xueshan; Yu, Huimin; Lin, Yao; Huang, Ke; Zhang, Jinyi; Zheng, Chengbin (Journal of hazardous materials, 2022)
Hexavalent chromium (Cr(VI)), a confirmed human respiratory carcinogen, has attracted widespread attention due to its high toxicity and mobility in natural water systems. However, the developed catalytic colorimetric probes for Cr(VI) detection remain challenging, such as various species of Cr(VI) coexisting in water or acid buffer, the obvious interference from oxidizing ions at acidic pH, the synthesis of complex materials, and the consumption of hydrogen peroxide. In this work, a phenomenon of UV light-triggered chromate to produce singlet oxygen under neutral pH was found. An environmentally-friendly method based on the rapid oxidation of chromogenic substrates was thus developed for the highly specific and accurate detection of Cr(VI). Cr(VI) serves as both the active center and the target of this system, which ensures the rapidity, simplicity, and environmental protection of the proposed colorimetric strategy. Importantly, the neutral catalytic condition ensures that the predominant species CrO42- can be accurately quantified and avoids the interference of oxidizing ions. Subsequently, a portable analytical system integrating an array of LED lamps, a miniature color reading device, and a developed smartphone-based program was successfully developed to accomplish high-throughput and on-site analysis of Cr(VI) in natural water. The proposed method provides a rapid screening and water quality assessment tool for the faster, more cost-effective, and accurate detection of Cr(VI) in the water system. [Display omitted] •The light-triggered oxidative activity of Cr(VI) at neutral pH was first proposed.•Cr(VI) is a green ionic photosensitizer that can generate singlet oxygen.•Accurate, selective, and environmentally-friendly analysis of Cr(VI) was obtained.•The portable colorimetric method is rapid, sensitive, and high throughput.•The developed colorimetric system can predict Cr(VI) pollution in natural water.